Habitat segregation of Gerres japonicus and G. limbatus in early stages in the Tien Yen estuary, Northern Vietnam - Tran, Thanh Trung; Tran, Hau Duc; Chu, Nam Hoang; Ta, Thuy Thi (Academia Journal of Biology, 2018)
Silver-biddy (Gerreidae: Gerres) are commercially important euryhaline fishes in coastal waters; however, information about their distribution during early stages in estuarine environments is poorly known. The present study aims to elucidate the habitat utilization of two species of the family, Gerres japonicus and G. limbatus as larvae and juveniles based on monthly collections from 2013 to 2015 in the Tien Yen estuary, northern Vietnam. They occurred from April to June for G. japonicus and in April and May for G. limbatus with a peak in May for both the species. Both G. japonicus and G. limbatus used the Tien Yen estuary as a nursery ground; however, the former species that colonized the shallows along the banks of the estuary extended to near freshwater habitat, whereas the latter was found at the end of the upper reach and the middle reach. The difference habitat use between the two species in the early life history may be related to their specific salinity preference as G. japonicus prefer lower salinities than G. limbatus.